Ward Heelers and Honest Men: Urban Québécois Political Culture and the Montreal Reform of 1909 - Gordon, Alan (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1995)
While scholars often emphasize traditionalism, ruralism and anti-statism as the "dominants" of Quebec's political culture prior to the Quiet Revolution, some Québécois embraced progressivism early in the twentieth century. Municipal government reform, one of the hallmarks of the progressive movement, cropped up in Canada's largest city, Montreal. Far from being confined to anglophones and remnants of Quebec's rouge party, support for reform came from a wide section of Montreal's French-speaking population. This article analyzes the rhetoric employed by Montreal's mass circulation newspapers during the referendum campaign of 1909 in order to demonstrate the popularity of reform in Montreal and to uncover the main doctrines of French-Canadian progressivism. Urban Quebec's political culture, then, accommodated the position of the city in Québécois culture and envisioned an expanding and active state role in city life. Overriding these beliefs were the basic assumptions of early-twentieth-century liberalism and, curiously for a referendum campaign, a distrust of popular sovereignty characteristic of North American reformism in general.